Nanoparticle Synthesis via Thin Film Ferroelectric Templates:Surface interactions and effects - Jones, Paul M. (Cranfield University, 2008)
An investigation into the processes taking place at the surface interface of ferroelectric Pb(Zr1-x,Tix)O3 immersed in metal salt solution under ultraviolet illumination is presented. The semiconducting and switchable dipolar nature of this material allows the spatial separation and control of photo-induced reduction and oxidation across its surface interface. These properties can be of application in novel techniques such as the controlled growth of metallic nanoparticles across specific polar domains. 70nm thick Pb(Zr0.3,Ti0.7)O3 samples, PZT(30/70), are manufactured using the sol gel methodology, two crystallographic orientations being produced. The orientation being controlled by the substrate used; Si was used for [111] orientation and MgO for [100]. The initial work with wideband ultraviolet light shows that the reduction and growth of silver on the PZT surface is greatly influenced by the structure of the film. The crystallographic orientation of the film affects metal deposition such that on [111] films the metal deposits only on positive domains, where as the [100] films experience deposition on both positive and negative domains. This is shown to be due to the difference in width of the space charge region, Δw = 4.4nm, between the [111] and [100] samples so that the negative domain on [100] samples have 10 19 times higher chance of electron tunnelling compared to the [111]. It is also shown that grain boundaries have the greatest effect on the growth of metal, with a metal cluster growth rate 51 times faster than elsewhere on the surface. This increased rate of growth is due to the effect a grain boundary has on the surrounding area, the energy band bending at the boundary attracting charge carriers from the grains around it. The interface types ranked from greatest to lowest influence are grain boundaries, positive domains, domain boundaries and finally interphase boundaries.ii It is shown that the stern layer, strongly adsorbed charged ions of opposite sign to the surface charge, at the PZT/solution interface act as an insulating layer to metal reduction. The accumulation of photoexcited charge carriers at points along grain boundaries causes the surface potential gradient to alter and allows metal reduction and thus clusters to nucleate. The energy required to cause this variation is investigated by use of narrow band, 5nm bandwidth, ultraviolet. For energy from 4.4eV to 5 eV, it is found there is an increase in the average silver cluster cross sectional area by a ratio of ca 1.6 to 1 for both the [111] and [100] orientations of PZT. Finally it is shown that the type of metal salt used in the photochemical process affects the type of reaction that takes place at the sample surface. For a cation to reduce on positive domains its reduction potential needs to be below the bottom edge of the conduction band of PZT. Chloride salts, that sit above the conduction band, cause decomposition of the negative domains. Use is made of these effects to find the position of the bottom of the conduction band for PZT. It is found that across similar [111] PZT samples FeCl2 can both reduce on positive domains and decompose negative domains, this puts the bottom of the conduction band for PZT(30/70) between 4.06 and 4.36 eV from vacuum. It is also discovered that the type of anion affects the decomposition of the negative domains. Nitrate salts with cations above the conduction band cause no decomposition whereas chlorides do. The decomposition is shown to be the loss of Pb from the negative surface.
Keywords: Semiconductor; Lead-Zirconate-Titanate; Grain Boundaries; Band Bending; REDOX